Wastewater : From Waste to Resource – The Case of Nagpur, India - World Bank (World Bank, Washington, DC, 2019)
Water stress has become a problem in most Indian cities, as rapid population growth increases simultaneously water demand by households, industries, and power plants. Utilities need to meet this growing demand while ensuring fair tariffs for users and promoting a sustainable use of water resources. As federal and state governments look for innovative alternatives to freshwater, the reuse of treated wastewater is gaining attention and being promoted at the federal and state levels. In addition to the environmental, health, and social benefits of treating wastewater; treated wastewater can become a reliable water source for industrial users, freeing up freshwater resources for households and helping address water scarcity in big cities. The government of India has taken steps to promote wastewater reuse, starting with the regulation of industrial water consumption and the setting and enforcement of mandatory water reuse targets for industries. The national target is to treat and reuse 50 percent of total wastewater by 2022 (PwC 2016). Some cities have set their own, more ambitious targets, and states such as Gujarat (Government of Gujarat, 2018) and Maharashtra (IndianExpress, 2017) have implemented new policies to promote wastewater reuse. Moreover, the government of India has adopted policies, established strong mechanisms of regulation, and provided funding for various programs, such as the Jawaharlal Nehru National Urban Renewal Mission (JNNURM), to enable municipal authorities to enter into public-private partnership (PPP) arrangements to attract private funding. As a result, municipalities across the country have started to implement wastewater reuse projects. Most of these initiatives are led by utilities, through partnerships with the private sector, and with the central government covering part of the capital costs. The success of these projects reveals that wastewater reuse activities can be viable if properly structured and supported by enabling policies and institutions.